Spontaneous postnatal complete resolution of an antenatally diagnosed fetal hepatic cyst: A case report. Issue 24 (June 2018) - Serban, Denis Mihai; Serban, Costela; Navolan, Dan; Sas, Ioan
Abstract: Rationale: Antenatal diagnosis of a fetal hepatic cyst is rare. Since in most cases the lesion is treated after birth by surgery only a few reports present a complete spontaneous resolution of an antenatally diagnosed hepatic cyst. Patient concerns: A single hepatic cyst (1.34/1.47 cm) was diagnosed in a fetus at 36 weeks of pregnancy while mother was in labor. After an uneventful vaginal birth, a multidisciplinary evaluation of the newborn confirmed the presence of the cyst. Diagnoses: Single hepatic cyst Interventions: Passive approach; periodic ultrasound monitoring of the cyst Outcomes: The latest ultrasound examination performed at 18 months of age confirmed complete resolution of the cyst. No other medical complications occurred before 18 months of age. Lessons: The management of such a case depends on the cyst dimensions, the types of involved structure and could require urgent prenatal or neonatal treatment. In our case a complete spontaneous resolution of the hepatic cyst was achieved before 18 months of age.